Implementasi Kebijakan Retribusi Tempat Khusus Parkir Di Kota Palangkaraya - Raden Biroum Bernardianto; Hairullah Hairullah (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2016)
This study aims to find out how the management of parking fees is managed by the transportation agency, starting from payments made by users of parking services to parking attendants, depositing to collection officers, receipt of treasurers then depositing to the city government so that it can be called city PAD (Regional Revenue) palangkaraya and contributions especially parking. The method used is a qualitative method, the research carried out is a descriptive study where the Department of Transportation and Office of Regional Original Revenue were chosen as the location of the study. Data collection techniques use observation, interviews, and documentation. The research results and discussion can be concluded that the implementation of the policy has not been maximized. This is because there are still some obstacles that hamper parking retribution faced by Palangka Raya Parking Area Revenues, especially in terms of collecting parking fees.